2021
DOI: 10.1016/s1470-2045(21)00376-4
|View full text |Cite|
|
Sign up to set email alerts
|

Talazoparib monotherapy in metastatic castration-resistant prostate cancer with DNA repair alterations (TALAPRO-1): an open-label, phase 2 trial

Abstract: Background Poly(ADP-ribose) polymerase (PARP) inhibitors have antitumour activity against metastatic castrationresistant prostate cancers with DNA damage response (DDR) alterations in genes involved directly or indirectly in homologous recombination repair (HRR). In this study, we assessed the PARP inhibitor talazoparib in metastatic castration-resistant prostate cancers with DDR-HRR alterations.Methods In this open-label, phase 2 trial (TALAPRO-1), participants were recruited from 43 hospitals, cancer centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 30 publications
(25 reference statements)
9
134
0
Order By: Relevance
“…While initially effective, patients with metastatic PCa receiving ADT will eventually develop resistance and progress to inevitably lethal metastatic castration-resistant prostate cancer (mCRPC) [ 4 ]. The last decade has seen an expansion of drugs to prolong the life of mCRPC, including second-generation androgen receptor (AR) inhibitors, the chemotherapeutic taxane cabazitaxel and PARP inhibitors for tumors with defects in DNA-damage-repair proteins such as BRCA1/2 and ATM [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, identifying new therapeutic targets for mCRPC patients and providing new genetic markers for existing therapies remain a critical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…While initially effective, patients with metastatic PCa receiving ADT will eventually develop resistance and progress to inevitably lethal metastatic castration-resistant prostate cancer (mCRPC) [ 4 ]. The last decade has seen an expansion of drugs to prolong the life of mCRPC, including second-generation androgen receptor (AR) inhibitors, the chemotherapeutic taxane cabazitaxel and PARP inhibitors for tumors with defects in DNA-damage-repair proteins such as BRCA1/2 and ATM [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, identifying new therapeutic targets for mCRPC patients and providing new genetic markers for existing therapies remain a critical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Breast and ovarian cancers respond to PARP inhibition when harboring HRR pathway deficiency. Talazoparib, a more potent PARP inhibitor than Olaparib and Rucaparib, is under study to test for efficacy against mCRPC with aberrant HRR [ 43 ]. Talazoparib is approved for HER2-negative breast cancer with germline BRCA1 / BRCA2 mutation.…”
Section: Current Prostate Cancer Therapiesmentioning
confidence: 99%
“…Studies have shown that PARP inhibitors may block prostate cancer disease progression to castration resistance prostate cancer, with reduced castration resistance growth and delayed development from local disease to mCRPC [ 111 ]. Furthermore, PARP inhibitors may also be effective in prostate cancer with genes indirectly involved in the HR pathway that are similar to BRCA mutations [ 119 ]. Several PARP inhibitors have been developed and investigated in clinical research, six of which are summarized in Table 2 .…”
Section: Implications For the Treatmentmentioning
confidence: 99%